Pengaruh Work-life Balance, Lingkungan Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan (Studi pada Generasi Milenial di Gading Serpong) - Jizra Dilano; Ririsma Sihombing; Gurpreet Dhillon; Bhily Bhily (Journal Of Business, Finance, and Economics (JBFE), 2022)
Employees are an added value for the company. They play a crucial role in achieving the company's vision and goals. To keep employee productivity optimal, it is important to pay attention to their satisfaction. One important factor in employee job satisfaction is creating a balance between work and personal life and creating a comfortable work environment. The research aims to determine the effect of work-life balance, work environment and job satisfaction on the performance of millennial generation employees in Gading Serpong. This type of research uses quantitative methods. The sampling technique uses a non-probability sampling technique with a simple random sampling method. The data collection method uses primary data obtained from questionnaires distributed to 150 millennial employee respondents in Gading Serpong who were used as research objects. The data analysis technique uses multiple regression analysis with t, F and R2 tests using SPSS 25. The results of this study indicate that work-life balance has an effect on employee performance, the work environment has an effect on employee performance, job satisfaction has an effect on employee performance and, Simultaneous Work-life balance, work environment and job satisfaction affect employee performance.